2018
DOI: 10.1186/s41065-018-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Variations in morphological traits of bermudagrass and relationship with soil and climate along latitudinal gradients

Abstract: BackgroundThis complex environmental heterogeneity coupled with the long-standing history offers scenario suitable for and favoring the evolution and existence of variation of morphological traits.MethodsIn this study, we measured 10 morphological traits of 310 Cynodon dactylon individuals sampled at 16 different locations along latitudinal gradients between 22°35′N and 36°18′N to reveal phenotypic plasticity influenced by latitude. In addition, the relationships between morphological variation and soil nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Bermudagrass is a widespread species that is adaptable to adverse environments that shows a contrary strategy in morphological traits to adapt to dry and low temperature conditions. However, high temperatures did not cause increases in plant size along a latitudinal gradient in another study [31].…”
Section: The Relationships Between Morphological Traits and Longitudementioning
confidence: 83%
See 3 more Smart Citations
“…Bermudagrass is a widespread species that is adaptable to adverse environments that shows a contrary strategy in morphological traits to adapt to dry and low temperature conditions. However, high temperatures did not cause increases in plant size along a latitudinal gradient in another study [31].…”
Section: The Relationships Between Morphological Traits and Longitudementioning
confidence: 83%
“…Morphological variation as a response to environmental changes at different geographic positions is common in C. dactylon [38,39]. A study of 260 accessions of bermudagrass germplasm indicated that there is extensive morphological variation in C. dactylon populations along longitudinal gradients, which has been found in some other studies [31,40,41]. The correlation analysis showed that the traits of width and dimeter were seldom significantly correlated with the longitude, soil nuriture or climate.…”
Section: The Relationships Between Morphological Traits and Longitudementioning
confidence: 92%
See 2 more Smart Citations
“…C. dactylon is an enormously variable and cosmopolitan warm-season turfgrass used for lawns, parks, and sports fields (Shi, Ye & Chan, 2013), which justifies new and innovative approaches toward evaluating and understanding the genetic relationships among different populations at different longitudes. Some studies have been used to analyze genetic diversity and population structure of bermudagrass because of its efficient dispersal and establishment abilities, rapid population growth, and phenotypic plasticity (Linder et al, 2018;Zheng et al, 2017;Zhang et al, 2018). Identifying the correlation between simple sequence repeat (SSR) markers and turf-quality-related traits among different bermudagrass populations can efficiently help to select high turf quality for bermudagrass.…”
Section: Introductionmentioning
confidence: 99%